Contraceptive Efficacy of Emergency Contraception with Levonorgestrel Given Before or After Ovulation - Croxatto -Avoni, H (2011)
Background: The contraceptive efficacy of emergency contraceptive pills containing levonorgestrel (LNG-EC) has been estimated in most previous studies by judging the day of ovulation from presumptive menstrual cycle data, thus providing poorly reliable estimates. Methods: In the present study, the efficacy of LNG-EC was determined in 393 cycles by dating ovulation on the basis of reliable hormonal and ovarian parameters validated by a database constructed in a separate study. In addition, the efficacy was determined separately for cycles in which LNG-EC was given before or after ovulation. Results: For the 148 women who had sexual intercourse during the fertile days, the overall accumulated probability of pregnancy was 24.7, while altogether 8 pregnancies were observed. Thus, the overall contraceptive efficacy of LNG-EC was 68%. Among the 103 women who took LNG-EC before ovulation (days -5 to -1), 16 pregnancies were expected and no pregnancy occurred (p